2019
DOI: 10.1530/joe-18-0503
|View full text |Cite
|
Sign up to set email alerts
|

Androgens modulate glucocorticoid receptor activity in adipose tissue and liver

Abstract: Glucocorticoid signaling is context dependent, and in certain scenarios, glucocorticoid receptors (GRs) are able to engage with other members of the nuclear receptor subfamily. Glucocorticoid signaling can exert sexually dimorphic effects, suggesting a possible interaction with androgen sex hormones. We therefore set out to determine the crosstalk between glucocorticoids and androgens in metabolic tissues including white adipose tissue, liver and brown adipose tissue. Thereto we exposed male C57BL/6J mice to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 44 publications
2
40
1
Order By: Relevance
“…The consequences of this on whole-body metabolism was not addressed in the aforementioned study, but another study revealed that corticosterone-induced metabolic derangements, such as BW gain and WAT expansion, were more severe in ovariectomized than in sham-operated female rats and were counteracted by estradiol supplementation (52). Recently, androgens were also reported to modulate GR activity in liver and adipose tissue of male mice (62). Although some signs/symptoms such as muscle wasting, osteoporosis, purple striae, and nephrolithiasis are more frequent in male patients with Cushing disease, the prevalence of metabolic derangements in Cushing syndrome, such as obesity and glucose abnormalities, does not differ between men and women (6365).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of this on whole-body metabolism was not addressed in the aforementioned study, but another study revealed that corticosterone-induced metabolic derangements, such as BW gain and WAT expansion, were more severe in ovariectomized than in sham-operated female rats and were counteracted by estradiol supplementation (52). Recently, androgens were also reported to modulate GR activity in liver and adipose tissue of male mice (62). Although some signs/symptoms such as muscle wasting, osteoporosis, purple striae, and nephrolithiasis are more frequent in male patients with Cushing disease, the prevalence of metabolic derangements in Cushing syndrome, such as obesity and glucose abnormalities, does not differ between men and women (6365).…”
Section: Discussionmentioning
confidence: 99%
“…The protection against dexamethasone-induced muscle wasting with α-actinin-3 deficiency specifically in female, but not male, mice is intriguing, given that similar changes in baseline protein synthesis and breakdown signalling were observed in both male and female Actn3 KO mice relative to WT. Dexamethasone has been shown to differentially affect gene expression in the livers of male and female rats (42), and this may be due to cross-talk between GR and other members of the steroid nuclear receptor subfamily, since both estrogen and androgen signalling modulates GR activity in various cell types and tissues (50, 51). α-Actinin-2, which is upregulated in α-actinin-3 deficiency, has been shown to influence androgen and estrogen receptor activities in vitro (34).…”
Section: Discussionmentioning
confidence: 99%
“…E, GR upregulates AR-target genes in absence of T in prostate cancer cells [ 79 , 80 ]. F, AR promotes GR-dependent gene expression in 3T3-L1s, brown adipose, and prostate cancer cells [ 80 , 82 , 95 ]. G, GR interferes with some AR-transcriptional end points in co-treatment in prostate cancer cells [ 80 ].…”
Section: Misprogramming Of Metabolism By Glucocorticoidsmentioning
confidence: 99%
“…T can upregulate 11β-hydroxysteroid dehydrogenase 1 ( 11β-HSD1 ) in omental adipose tissue from children [ 94 ], suggesting that AR crosstalk with GR can also be mediated by altering tissue GC availability because 11β-HSD1 catalyzes the activation of GCs from inactive precursors. DHT and corticosterone co-treatment in white and brown adipose tissues resulted in amplified upregulation of GR-dependent genes that were not upregulated with DHT alone, whereas AR antagonism decreased GR transcriptional activity in adipose and the liver [ 95 ]. Finally, androgens were shown to sensitize mice to GC-mediated lipid accumulation and insulin resistance, suggesting that androgen action cross-talks with GCs in metabolically important tissues [ 96 ].…”
Section: Glucocorticoid and Androgen Receptor Crosstalkmentioning
confidence: 99%